PENGARUH TEKNIK PROBING-PROMPTING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA PESERTA DIDIK KELAS XI MIPA SMAN 4 PADANG - AFRIZALDO . (Departemen Matematika, 2020)
The development of science and technology today cannot be separated from the role of the mathematics. One of the main goals of mathematics in school is to train students in solving mathematical problems in everyday life. In the reality found at SMAN 4 Padang, students’mathematical problem solving abilities are still relatively low. This study looks at the effect of probing-prompting technique in mathematics learning to improve students’ mathematical problem solving abilities compared to direct learning that has been applied so far. The method used in this study is the quasi experiments method with the design of Randomized control Group Only Design. Based on data analysis the result of final test problem solving in the form of essays conclude the influence of probing-prompting technique resulted in the test result of students’ problem solving ability of the experimental class better than the control class. Keywords: Probing-prompting, mathematical problem solving, direct learning.